2006
DOI: 10.1093/ajcn/84.2.414
|View full text |Cite
|
Sign up to set email alerts
|

Calcium retention in adolescent boys on a range of controlled calcium intakes

Abstract: The higher calcium retention in boys than in girls was attained through higher net calcium absorption and lower urinary excretion than in girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 11 publications
0
34
0
2
Order By: Relevance
“…Subjects and study design A pilot study was conducted as an adjunct to a metabolic study following methods that have been described earlier (Braun et al, 2006(Braun et al, , 2007. Owing to the objectives of the primary study, participants (n ¼ 31) were 16 boys and 15 girls of Chinese heritage between the ages of 11 and 15 years.…”
Section: Methodsmentioning
confidence: 99%
“…Subjects and study design A pilot study was conducted as an adjunct to a metabolic study following methods that have been described earlier (Braun et al, 2006(Braun et al, , 2007. Owing to the objectives of the primary study, participants (n ¼ 31) were 16 boys and 15 girls of Chinese heritage between the ages of 11 and 15 years.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the positive calcium balance in adolescents (e.g., mean age 13 yr) is achieved by higher levels of bone formation, resorption, net bone calcium retention and absorption and lower urine calcium compared with those of young adults (e.g., mean age 22 yr) in neutral balance ( Figure 1A). Sex (13) and race (14) variations in calcium balance in adolescents have also been identified. This can be seen in black American adolescents, who have higher rates of calcium absorption, increased net skeletal calcium retention, and lower urine calcium than white American adolescents ( Figure 1B) (14).…”
Section: Calcium Distributionmentioning
confidence: 99%
“…This result suggests that high calcium absorption may facilitate fat absorption and contribute to weight gain, and only when a change in fecal calcium is .0.4 g/d will the fecal fat excretion increase. We previously reported the relation between fecal calcium excretion and calcium intake and observed that such a large increase in fecal calcium could occur at very high calcium intakes (ie, .1500 mg/d) (24,27) or after completion of puberty. Calcium retention is also influenced by BMI.…”
Section: Discussionmentioning
confidence: 99%